About influenza and flu vaccination: opinion the students’ medical school V.V. Balzhieva, L.A. Khlebnik - V. V. Balzhieva; L. A. Khlebnikova (Журнал инфектологии, 2025)
The level of vaccination of current and future health workers (students) is insufficient. Influenza vaccination is a measure aimed at preventing the disease itself, reducing the likelihood of adverse public health consequences, and minimizing the risk of involvement in a pandemic. Immunized health care workers interrupt the pathways of infection, are less susceptible to infection and further transmission to their immediate environment. In some cases, a health worker’s personal belief in the low effectiveness of the influenza vaccine may be reflected in low adherence to immunization among patients and like-minded colleagues. During the training phase, medical students should be motivated and convinced of the importance, efficacy and safety of vaccination.Aim of the study: to analyze the current level of knowledge about influenza and influenza vaccination among undergraduate medical college students Materials and methods. A sociological survey of undergraduate students of medical college conducted to analyze the current level of knowledge about influenza, attitudes towards influenza vaccination and to assess the respondents’ opinion about the effectiveness of vaccine prevention.Results. More than 60% of students consider influenza vaccination to be a professional obligation. Five% of respondents believe that vaccination is more dangerous than the disease and is associated with side effects. The majority of respondents (36%) indicate that the post-vaccination period is not a cause for concern. 312 students (64.19%) vaccinated in the last 5 years. The multiplicity of vaccination among medical students amounted to: five cases – 175 (36.01%), 4 – 38 (7.82%), 3 – 37 (7.61%), 2 – 36 (7.41%), 1 – 26 (5.35%), not vaccinated – 24 (4.94%). It is also important to note this result of the survey: 269 students believe that they infected with influenza (55, 35%). Regarding the issues of influenza epidemiology, students demonstrated an average level of knowledge.Conclusion. A sociological survey shows an average level of knowledge about influenza and vaccination among medical college students.